IMPLEMENTING PRIMARY EYE-CARE IN PRIVATE PRACTICES MALAYSIA; THE INTERNAL CHALLENGES PERCEIVED BY THE OPTOMETRISTS - Yahaya, Nurul Ain; Musa, Azuwan; A. Rahman, Nor Azlina (International Journal of Allied Health Sciences, 2021)
Background: In Malaysia, the role of optometrists in the private sector is limited compared to their counterparts elsewhere. Primary eye care is still not widely offered in private practices despite its demand to reduce the public’s eye morbidity. The purpose is to explore the challenges perceived by the private sector optometrists to implement primary eye care in Malaysia. Methodology: In-depth interview using semi-structured open-ended questions was designed to explore the challenges perceived. Fifteen private optometrists across Malaysian were interviewed via purposive sampling until the data-saturated. The interviews were audio-recorded, transcribed and analyzed. Results: The internal challenges of implementing primary eye-care in private practices in Malaysia consists of four major themes emerged; financial struggles, issues on competency, attitudes and time. All of the respondents mentioned the high cost involved in implementing primary eye care. Many agreed that primary eye-care is time-consuming and requires a competent and highly motivated optometrist. Lastly, attitudes place the most significant role in implementing primary eye- care in Malaysia. Conclusion: The information gathered are important to address the challenges perceived by the optometrists to implement primary eye care. Keywords: Primary eye-care, optometrists, private sector, challenges